2014
DOI: 10.1093/abbs/gmu034
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine dithiocarbamate protects pancreatic β-cells from oxidative damage through regulation of FoxO1 activity in type 2 diabetes rats

Abstract: Pyrrolidine dithiocarbamate (PDTC) can lower the blood glucose level and improve the insulin sensitivity in diabetic rats. However, the mechanisms underlying this effect of PDTC treatment in diabetic rats remained uncertain. In this study, we evaluated the mechanisms by which PDTC conferred protection against oxidative damage to pancreatic islet b-cells in rats with experimental type 2 diabetes mellitus (DM). DM in the rats was elicited by long-term high-fat diet accompanied with a single intraperitoneal (i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Consequently, PDTC reduces the production of inflammatory cytokines. 13 Protective role of PDTC against I/R injury was the main concern of the current study. Previous reports have documented the beneficial effects of PDTC in testicular injury due to cisplatin, renal damage attributed to extracorporeal shock wave lithotripsy, acute respiratory distress syndrome, and focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, PDTC reduces the production of inflammatory cytokines. 13 Protective role of PDTC against I/R injury was the main concern of the current study. Previous reports have documented the beneficial effects of PDTC in testicular injury due to cisplatin, renal damage attributed to extracorporeal shock wave lithotripsy, acute respiratory distress syndrome, and focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 89%
“…Studies have shown that inactivation of FOXO1 contributes to β-cell protection under oxidative damage ( Ding et al, 2014 ; Shao et al, 2014 ). It is known that in β-cells FOXO1 acts as a negative regulator of PDX1 functions and mediate β-cell dysfunction and apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK/mTOR signaling mediates protecting β-cells against diabetic oxidative stress ( Wang et al, 2016 ). Oxidative stress also induces activation of FOXO1 which suppresses the function of PDX1 to reduce insulin expression consequently ( Ding et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deacetylated FoxO1 protects β‐cell function by limiting mitochondrial lipid utilization through decreasing fatty acid oxidation and enhancing insulin secretion in the context of diabetes (Kim‐Muller et al, ); which is in consist in the findings that the levels of acetylated FoxO1 are markedly increased in pancreatic tissues of diabetic, compared to healthy rats (Ding et al, ). We found elevated levels of acetylated FoxO1 in the pancreatic β‐cells exposed to the HDAC4 mutations compared to the wild type, indicating the failure of FoxO1 deacetylation in the diabetic patients.…”
Section: Discussionmentioning
confidence: 98%